Trends in hospital standardized mortality ratios for stroke in Japan between 2012 and 2016: a retrospective observational study. (28th October 2019) - Amin, Rebeka; Kitazawa, Takefumi; Hatakeyama, Yosuke; Matsumoto, Kunichika; Fujita, Shigeru; Seto, Kanako; Hasegawa, Tomonori
Abstract: Objective: Stroke is one of the leading causes of death and disability, and imposes a major healthcare burden. The aim of this study was to determine the characteristics of hospital standardized mortality ratios (HSMRs) for stroke in Japan for the year 2012–16 to describe the trend. Design: Retrospective observational study. Setting: Data from the Japanese administrative database. Participants: All hospital admissions for stroke were identified from diagnostic procedures combination (DPC) database from 2012 to 2016. Main Outcome Measures: HSMR was calculated using the actual number of in-hospital deaths and expected deaths. To obtain the expected death number, a logistic regression model was developed to get the coefficient with a number of explanatory variables. Predictive accuracy of the logistic models was assessed using c-index and calibration was evaluated using the Hosmer–Lemeshow test. Results: A total of 63 084 patients admitted for stroke from January 2012 to December 2016 were analyzed. HSMRs showed declining tendency over these 5 years, suggesting stroke-related mortality has been improving. While the HSMRs varied from year to year, a wide variation was also seen among the different hospitals in Japan. The proportion of hospitals with HSMR less than 100 increased from 41.0% in 2012 to 59.0% in 2016. Conclusion: This study demonstrated that HSMR can be calculated using DPC data and found wide variation in HSMR of stroke among hospitals in Japan and enabled us to image the trend. By examining these trends, facilities, authorities and provinces can initiate designs that will ultimately lead to an upgraded healthcare delivery system.